Remarks at the Fragility Forum 2016 - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed the vision of a world free of poverty by 2030, resolving to boost the prosperity of the bottom 40 percent of the population in developing countries. Addressing the root causes of conflict and insecurity is a core priority of the World Bank Group. He raised six questions and challenges. First, fragility is no longer mostly limited to low-income states. Second, weak states have great difficulty delivering services to their citizens. Third, development and humanitarian groups have long worked separately. Fourth, refugees are no longer largely living in camps. Fifth, we now know that we will not have enough ODA – official development assistance – to pay for helping communities and refugees. Sixth, we don’t know enough about the refugees themselves.